PENERAPAN MODEL PBL TEMA 7 UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 3 SDN GUNUNG GEDE - Fitria Suci Martind; Nita Karmila; Rahayu Kartika (STKIP Subang, 2023)
ABSTRACT The purpose of this study is: (1) to learn the process of applying the model of the based learning problem (PBL) to enhance learning in class III.A elementary school Gunung Gede Bogor City. (2) to find an increase in the results of learning the 7 theme